Development and validation of a stability-indicating RP-HPLC method for tizanidine hydrochloride using DOE - Gunjal, Prasad; Patel, Janki (Journal of Applied Pharmaceutical Research, 2025)
Background: Tizanidine hydrochloride (TIZ) is a centrally acting α2-adrenergic receptor agonist widely prescribed for managing spasticity. Given its therapeutic importance, a reliable, stability-indicating analytical method is crucial to ensure both the quality and regulatory compliance of Tizanidine hydrochloride. Existing RP-HPLC methods often lack robustness, sensitivity, or DoE optimization, highlighting the need for an improved approach. Methodology: A stability-indicating reverse-phase high-performance liquid chromatography (RP-HPLC) method with stability-indicating properties was developed and validated using a Design of Experiments (DoE) approach. A full factorial design was implemented, optimizing mobile phase composition and flow rate as key method variables. Chromatographic separation was achieved using an Agilent Zorbax Bonus RP column (250 × 4.6 mm, 5 µm) with a mobile phase of 0.1% trifluoroacetic acid (TFA) and acetonitrile (65:35 v/v) at a 0.5 mL/min flow rate. Detection was performed at 228 nm. The method was validated by ICH guidelines, evaluating parameters such as specificity, precision, accuracy, linearity, robustness, and forced degradation. Results and Discussion: The method demonstrated excellent linearity (r² = 1.00) across concentration levels ranging from 80% to 120% of the target concentration. The LOD and LOQ were 1.00 µg/mL and 3.04 µg/mL, respectively. High precision (%RSD < 2%) and accuracy (99–101% recovery) were observed. Forced degradation studies revealed notable degradation under oxidative (36.08%) and acidic (15.73%) conditions. Conclusion: The developed RP-HPLC method is precise, robust, and suitable for the routine quality control and stability assessment of Tizanidine hydrochloride in pharmaceutical formulations.